Parapharyngeal space tumors: a ten year experience at a tertiary care hospital - Sarwar, Mirza Muhammad; Riaz, Muhammad; Javaid, Waqas (Journal of Fatima Jinnah Medical University, 2019)
Background: Paraphyrangeal space is a potential space around the pharynx. Most of the tumors of this space are benign. Surgery is the mainstay of treatment of these tumors. The aim of this study is to review our experience of management of these tumours and to revisit the surgical approaches used for their management. Subjects and methods: This retrospective study included 15 patients who were managed at ENT Department Sir Ganga Ram Hospital/ Fatima Jinnah Medical College, Lahore over a period of 10 years from October 2007 to October 2017. Their diagnosis was made on detailed history, clinical examination and relevant investigations. There were 9 males and 6 females out of total 15 patients. Their age range was between 22 to 54 years with a mean age of 37 years. We used three approaches for excision. Transoral approach was used for smaller pleomorphic adenomas while other two approaches were employed for medium to large sized tumors. The hospital stay was between 5-8 days. Results: Twelve cases proved to be pleomorphic adenoma while two cases were schawanoma and one was a case of lymphatic malformation. All these patients were treated surgically through different approaches. Two patients developed palatal paresis which recovered after one year. One patient had change of voice due Left vocal cord paresis which recovered after six months. Three patients developed small sized haematomas which were treated conservatively. Conclusion: Most of the tumours of PPS are benign. Surgery is the preferred way of treating PPS tumours. Although trans-cervical is the most frequently used approach, small tumours of PPS can be removed transorally while for very large tumours transmandibular-oropharyngeal approach should be applied.